The effects of chemotherapy agents on hypoxia in colorectal cancer - Siddiky, A (2015)
Tumour hypoxia describes the phenomenon of reduced oxygen tension within solid tumours, resulting in an increase in morbidity, mortality and metastasis. We aim to identify chemotherapy agents that may reduce oxygen consumption and ultimately, improve tumour hypoxia and radiosensitivity. Four colorectal cancer cell lines (COLO320DM, DLD1, HCT116 and HT29) and a nontransformed cell line (MRC5) were investigated. Clonogenic and cytotoxicity assays of a range of agents were used to determine sub-lethal concentrations that would alter consumption without cytotoxicity. The oxygen consumption and mitochondrial function of treated cells were assessed with the XF96 Analyzer. Flow cytometry, high performance liquid chromatography and western blot were performed to delineate mechanisms of action. The most responsive cell lines were grown as spheroids for hypoxia modelling before being tested in vivo for radiation sensitivity. In vivo tumour hypoxia analysis was achieved with the in vivo imaging system. The oxygen consumption of all cancer cell lines was markedly reduced after treatment with a number of the agents compared to the non-transformed cell line. DLD1 and HCT116 cell lines showed the greatest balance of resistance to toxicity and reduction in oxygen consumption. Hypoxia imaging of the subsequent spheroids and in vivo tumours further demonstrated a reduction in hypoxia consistent with drug induced decrease in oxygen consumption. This also conferred a relative enhancement in radiosensitivity in both in vitro and in vivo settings. Despite decades of clinical use these known chemotherapeutics have not been implicated in alterations in oxidative metabolism. These results raise the prospect of using them in an alternative way to potentially improve clinical outcome.